Evaluation of tensile shear strength for dissimilar spot welds of Al-Si-Mg aluminum alloy and galvanized steel by delta-spot welding process - Kim, Young-Gon; Kim, Dong-Cheol; Joo, Sung-Min (Journal of mechanical science and technology, 2019)
According to the conventional studies, it was difficult to perform the dissimilar spot welding between aluminum alloy and steel. In this research, delta-spot welding was performed to evaluate the dissimilar weldability and mechanical properties of the Al 6061-T6 and GA440 steel sheets. A spot welding experiment was carried out varying process parameters. Also, the tensile shear strength was evaluated at each condition, and cross-sectional observation of the weld zone was performed with an electron microscope. The strength of the dissimilar spot welds decreased with increasing force, and increased in proportion to the weld time and current. As a test result of the influence of types of the process tapes, PT1407, which has a relatively higher heat input than PT2000, showed higher strength of the dissimilar spot welds. Especially, the Fe-Al intermetallic compounds (IMC) layer was less than 3 μm thick. It was thick at the center of the nugget and thin at the edge depending on the heat input.